‘The Lehman Brothers Bailout and its Subsequent Regulatory Responses: Should the bailout have occurred and can regulation mitigate bailout incentivisation issues?’ - Cottrell, Sam (2010)
The global economy currently contends with the greatest threat to the stability and continuation of the financial and economic markets since the Great Depression. The seeds of the crisis were sown within the sub-prime mortgage market in 2006. It escalated and engulfed the U.S. finance sector in 2007 and during 2008 contaminated the global real economy. One of the landmarks of the crisis’ timeline is the collapse of Lehman Brothers Investment Bank. The decision not to bail out the firm has been the topic of unrelenting debate since the history weekend of September 15th 2008. Within this paper it will be purported that Lehman should undeniably have been subject to a government bailout, eliminating the trigger for a colossal market shock. It will be demonstrated that it is possible to mitigate many of the negative facets to a bailout, such as issues with incentivisation, and that Walter Bagehot’s 1873 proposal of liquidity provision is essentially still relevant to the current crisis. An elastic, immediate supply of liquidity in conjunction with some form of regulatory penal scheme can provide a future framework to be applied when the next crisis occurs and mass bankruptcy looms. The paper will take the following structure. A general financial crisis will be defined and its macroeconomic characteristics outlined. Subsequently the causes pertinent solely to the collapse of Lehman’s will be delineated, contextualized by the previous chapters and the impact of Lehmans failure on several markets will be used to irrefutably demonstrate some form of bailout was desirable. The crux of the article will centre around the debate regarding a bailout, and upon the long-term regulatory or legislative methods by which the negative externalities associated with bailouts may be marginalized.